2016
DOI: 10.1016/j.jep.2016.08.022
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic activities of cardenolide glycosides from Asclepias subulata

Abstract: In this study was found that cardenolide glycosides, 12, 16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside and desglucouzarin, isolated from A. subulata induced the cell death trough caspase-dependent apoptosis, which was activated, preferably, by extrinsic pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…In recent years, numerous cardenolides have shown apoptosis through caspase-dependent apoptosis including (+)-strebloside, 15 12,16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside, desglucouzarin, 25 periplocymarin, and periplocin. 26 Additionally, selected cardenolides have entered phase I and II clinical trials for the treatment of solid tumors with satisfactory safety and efficacy profiles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In recent years, numerous cardenolides have shown apoptosis through caspase-dependent apoptosis including (+)-strebloside, 15 12,16-dihydroxicalotropin, calotropin, corotoxigenin 3-O-glucopyranoside, desglucouzarin, 25 periplocymarin, and periplocin. 26 Additionally, selected cardenolides have entered phase I and II clinical trials for the treatment of solid tumors with satisfactory safety and efficacy profiles.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The extracts and secondary metabolites isolated from several parts of this plant have been reported to exhibit a range of pharmacological activities, including anti-inflammatory [ 10 ] and anticancer effects [ 4 , 6 ]. Compounds isolated from the milkweed plants (family: Apocynaceae or Asclepedaceae), such as 12,16-dihydroxycalotropin, calotropin, corotoxigenin 3-O-glycoside, desglucouzarin, uscharin, and 2′′-oxovoruscharin, have been explored as potential anticancer agents, owing to their ability to induce cell death through apoptosis and other pathways [ 11 13 ]. Recently, an ethanolic extract of the aerial parts of C .…”
Section: Introductionmentioning
confidence: 99%
“…According to Mo et al (2016) , calotropin activates the mitochondrial apoptotic pathway, accompanied by an increase in Bax/Bcl-2 ratio, decreased mitochondrial membrane potential, and increased reactive oxygen species (ROS) production and activation of caspases 3 and 9. Rascón-Valenzuela et al (2016) reported that calotropin and C3OG induce apoptosis by caspases 3, 8, and 9 activating the A549 cell line. Malayoside is a cardenolide with a similar structure to C3OG, which showed a cytotoxic and apoptotic effect on the NCI-H460 lung cell line.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed selective cytotoxicity by not significantly affecting the non-cancerous human cell line and the murine cancer cell line ( Rascón-Valenzuela et al, 2015 ). Additionally, these cardenolides induced cell death through caspase-dependent apoptosis, activated by an extrinsic pathway ( Rascón-Valenzuela et al, 2016 ). Furthermore, recent studies have shown that calotropin inhibits the enzymatic activity of the Na + /K + -ATPase ( Pederson et al, 2020 ; Agrawal et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%